Values and Principles Informing Designs for People Living With Dementia-an Emerging International Consensus - Fleming, Richard; Bennett, Kirsty A.; Zeisel, John (Journal of aging and environment, 2023)
This article provides a perspective on the development of an international consensus on the values and principles guiding building designs that enable people living with dementia to live full lives. A manifesto based on views contained in the Alzheimer's Disease International World Alzheimer's Report 2020; Design, Dignity, Dementia was published on the web. Signatories were asked to comment on the values and principles it contained. Comments from signatories in 18 countries were thematically analyzed and the values and principles refined in light of the findings. The refined manifesto was then published. There is an emerging international consensus on the values and principles that should be applied when designing to afford people living with dementia the dignity, autonomy, independence, equality of opportunity and nondiscrimination that is their right.